(untitled) (Research, Society and Development, 2021)
The aim of this review was to describe the main characteristics, bottlenecks, signs and trends that the artisanal fishing sector presents in the different environments where it occurs in Brazil, whether marine or continental environments. It also points out the possible strategic directions of Brazilian Agricultural Research Corporation- Embrapa in order to contribute to give more visibility to this production chain and to integrate research, development and innovation. Innovative strategies such as the ecosystem approach, even though they are still timid in Brazil, appear as a possibility of navigating “Blue Oceans” in which, the search for unexplored markets translates into fostering strategies to reconcile sustainable catches, conservation, respect for socioeconomic dynamics and the strengthening governance through the participation of fishermen in decision-making. A global and Brazilian review of the sector is also outlined, as well as Embrapa’s participation in this context. Finally, we highlight some possible ways in which Embrapa operates in the artisanal fisheries production chain, such as operating in marine environments, aggregating internal expertise at the Company, using HUB models of action and promoting research with an ecosystemic approach. Regardless of the path to be followed, it is necessary to change the mentality in dealing with this target audience, using participatory approaches and working in collaborative networks with strategic partners. In order to navigate the longed-for “Blue Ocean”, and leave behind the “Red Ocean” of uncertainty, the vision of the future necessary for advancing on the frontier of knowledge may place Brazil on exemplary levels of fisheries management.